Answer :

We have,

x4 + 2x3 – 3x2 + x - 1


Let, p (x) = x4 + 2x3 – 3x2 + x - 1


And, x - 2 = 0


x = 2


It is given that, (x - 2) is a factor of p (x) so the remainder is equal to p (2)


p (2) = (2)4 + 2 (2)3 – 3 (2)2 + 2 - 1


= 16 + 16 – 12 + 2 – 1


= 34 – 13


= 21


Hence, option D is correct

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

In each of the foRD Sharma - Mathematics

In each of the foRD Sharma - Mathematics

When (x31</sRS Aggarwal & V Aggarwal - Mathematics

Find the remaindeRS Aggarwal & V Aggarwal - Mathematics

When p (x) = (x<sRS Aggarwal & V Aggarwal - Mathematics

If p (x) = 2x<supRS Aggarwal & V Aggarwal - Mathematics

If (x3RS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

(x +1) is a factoRS Aggarwal & V Aggarwal - Mathematics